Essential Excel 2019 : a step-by-step guide - Slager, Annette; Slager, David (Apress, 2020)
Create, edit, sort, analyze, summarize, and format data as well as graph it in Excel 2019. Chock full of visuals, user-friendly instructions, and reader exercises, this in-depth guide makes it easy for you to get on the bandwagon taking advantage of this powerful software and what it can do. Essential Excel 2019 doesn't mess around. It provides the most clear and concise, but complete, information you need to successfully use the expansive features of Excel in your work environment. The second edition of this soup-to-nuts book delivers essential how-to and reference information for users who are new to Excel, those who want to continue building their Excel skills, or anyone who wants to get up to speed on the latest changes and features in Excel 2019. It is heavy on the practical examples and light on the theory, providing a step-by-step process of what you need to do when you are working with Excel. You will begin with the basics, advancing as each chapter builds on knowledge from previous chapters. You will appreciate real-life examples and exercises that reinforce what you have learned, and upon finishing the book, you will have the confidence to use much more than the typical 10% that most people use in Excel. What You Will Learn Create amazing visualizations of your data Get up to speed on easy and accurate methods for entering data Extract the information you want from imported data; manipulate and format it to meet your needs Export your results to other programs or share with others in the cloud Organize, summarize, filter, and consolidate your data in multiple ways Audit, validate, and protect your data Who This Book Is For Anyone new to Excel or looking to take better advantage of the advanced features of the platform.